2023
DOI: 10.3390/en16093804
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and Microstructural Characteristics of Clay Minerals and Their Effects on the Pore Structure of Coal-Measure Shale: A Case Study in Qinshui Basin, China

Abstract: As the essential component of shale, clay minerals have a vital influence on the pore structure and the gas content of reservoirs. To investigate the compositional characteristics of coal-measure shale and its effects on pore structure, a total of thirteen Taiyuan formation shale samples were collected from the Qinshui Basin and were analyzed using a combination of X-ray diffraction analysis, X-ray fluorescence spectrometry, Fourier transform infrared spectroscopy (FE-SEM), polarized optical microscopy, and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…This result is obviously different from previous research on clay minerals. For example, Ji et al [86,87] documented that micropores in chlorite and illite (both of them are present in theYC2 samples, see Table 2) were underdeveloped, and their pores were dominated by pores with a size of 20-100 nm (mesopores and macropores); Li et al [88] suggested that 2-50 nm pores in clay minerals provided their main pore volume and specific surface area. Considering that the porosity of the YC2 samples is mainly controlled by the clay minerals (Figure 6c), it can be further deduced that the tectonic deformation resulted in a significant reduction in mesopores in clay minerals, with the formation of some larger deformation macropores and the transformation into micropores.…”
Section: Pore Structure Parameters and Their Controlling Factorsmentioning
confidence: 99%
“…This result is obviously different from previous research on clay minerals. For example, Ji et al [86,87] documented that micropores in chlorite and illite (both of them are present in theYC2 samples, see Table 2) were underdeveloped, and their pores were dominated by pores with a size of 20-100 nm (mesopores and macropores); Li et al [88] suggested that 2-50 nm pores in clay minerals provided their main pore volume and specific surface area. Considering that the porosity of the YC2 samples is mainly controlled by the clay minerals (Figure 6c), it can be further deduced that the tectonic deformation resulted in a significant reduction in mesopores in clay minerals, with the formation of some larger deformation macropores and the transformation into micropores.…”
Section: Pore Structure Parameters and Their Controlling Factorsmentioning
confidence: 99%